Preparation and characterization of high initial bonding strength reactive hot melt polyurethane adhesive derived from phthalate polyester polyols. Issue 20 (18th October 2018) - Yan, Qiming; Lin, Zhongxiang; Lin, Xing; Fang, Cheng
Abstract: A series of phthalate polyester polyols (PEs) were synthesized via a polycondensation reaction with phthalic anhydride (PA) and different glycols, such as neopentyl glycol (NPG), ethylene glycol (EG), diethylene glycol (DEG), 2-methy-1, 3-propanediol (MPO), 1, 4-butylene glycol (1, 4-BDO) and trimethylolpropane (TMP). Reactive hot melt polyurethane adhesive (HMPUR) with high initial bonding strength was then prepared by poly(propylene glycol) 2000 (PPG-2000), Dynacoll 7360 with these resultant PEs. Effects of different glycols on the glass transition temperature ( T g ) and viscosity of the PEs were investigated. Besides, influences of these resultant PEs on the water resistance, bonding strength, thermal stability and surface morphology of the HMPUR were further discussed. The experimental results showed that T g and viscosity of the PEs decreased with the increase of the chain flexibility of diols. The initial bonding strength of the HMPUR increased with the increase of T g of the PEs. The hydrogen bonds and cross-linking structure of the HMPUR will also lead to the increase of the bonding strength. In addition, the water resistance of HMPUR was improved by the cross-linking structure and lateral methyl groups of the PEs, while the thermal stability changed little. The surface morphology of the HMPUR showed that all samples have two phase structures and the HMPUR based on DEG and 1, 4-BDO exhibited weak phase separation.